The Effect of the Tax Volunteer Program on the Tax Literacy Level of Individual Taxpayers: A Literature Study and Case Study of KPP Pratama Kembangan - Putri Permata Sari; Iwan Harefa; Yananto Mihadi Putra (Countable (Contemporary Business and Sustainability Science), 2025)
The "Tax Volunteer for the Country" (Renjani) program is an initiative by the Directorate General of Taxes in collaboration with higher education institutions aimed at enhancing public tax literacy and compliance through student involvement as educational agents. This article explores the extent to which the Renjani program influences the level of tax literacy among Individual taxpayers at KPP Kembangan and its relevance to tax planning and tax accounting practices. This study employs a qualitative method through literature review, referring to six relevant academic articles. Findings indicate that direct involvement of tax volunteers in providing education, e-filing assistance, and disseminating tax regulations significantly improves taxpayers' understanding of their rights and obligations. This enhanced tax literacy supports more structured and lawful tax planning practices, such as avoiding administrative sanctions and improving filing efficiency.